2021
DOI: 10.1021/acs.biomac.1c01056
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites Assembled via Electrostatic Interactions between Cellulose Nanocrystals and a Cationic Polymer

Abstract: On account of their high strength and stiffness and their renewable nature, cellulose nanocrystals (CNCs) are widely used as a reinforcing component in polymer nanocomposites. However, CNCs are prone to aggregation and this limits the attainable reinforcement. Here, we show that nanocomposites with a very high CNC content can be prepared by combining the cationic polymer poly[(2-(methacryloyloxy)ethyl) trimethylammonium chloride] (PMETAC) and negatively charged, carboxylated CNCs that are provided as a sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…These findings confirm that the addition of CNCs and PDA to the cathodic PA matrix can reduce the penetration rate of corrosive electrolytes to metallic substrates. They further demonstrate good barrier properties of the electrodeposited PA-CNC and PA-CNC-PDA nanocomposite coatings and prove their dense and homogeneous structure via the formation of strong interfaces between CNCs, PDA and PA matrix caused by electrostatic 28 and hydrogen bonding interactions. 19…”
Section: Electrochemical Properties Of Coated Hsla Steelmentioning
confidence: 62%
See 3 more Smart Citations
“…These findings confirm that the addition of CNCs and PDA to the cathodic PA matrix can reduce the penetration rate of corrosive electrolytes to metallic substrates. They further demonstrate good barrier properties of the electrodeposited PA-CNC and PA-CNC-PDA nanocomposite coatings and prove their dense and homogeneous structure via the formation of strong interfaces between CNCs, PDA and PA matrix caused by electrostatic 28 and hydrogen bonding interactions. 19…”
Section: Electrochemical Properties Of Coated Hsla Steelmentioning
confidence: 62%
“…It is reported that when the absolute value of the ζ -potential is above 30 mV for colloidal suspensions, the particles are electrically stable in the suspension. 28,37 Despite the drop observed in ζ -potential after CNC addition, the values remain positive and above +30 mV even at the highest CNC concentration indicating a stable positively charged PA–CNC dispersion. On the other hand, the particle size steadily increases from 130.4 ± 0.7 nm to 149.7 ± 9.1 nm with increasing CNC concentration (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high crystallinity and well-defined high aspect ratios of cellulose nanocrystals (CNCs) when used as fillers induce excellent mechanical properties in polymer matrices. Like other colloidal rods, such as DNA fragments and chitin nanocrystals, CNC suspensions show interesting properties of a liquid crystal. , At above critical concentration, the CNC suspension phase separates into an upper isotropic phase and a lower anisotropic chiral nematic phase. This concentration-dependent phase transition leads to research questions related to how addition of moieties, salts, or polymer influences the structural transition of CNCs. CNC stabilization in suspensions and underpinning their interactions with other entities or particles enable their use for a wide range of applications, such as catalysis, self-healing membrane technologies, or conductive thin films. …”
Section: Introductionmentioning
confidence: 99%